Abstract 105: Limb Shaking Transient Ischemic Attack: A Rare Presentation of Internal Carotid Artery Occlusion - Francesca Pastrana; Wilson Rodriguez; Divya Singh; Hanan Qaqish; Brian Miremadi (Stroke: Vascular and Interventional Neurology)
Introduction Limb‐shaking transient ischemic attack (LS‐TIA) is a rare disorder characterized by brief, irregular, involuntary movements of the extremities with or without loss of consciousness. Associated paroxysmal hyperkinetic extremity movements often described by patients as “shaking,” “tremors,” or “twitching” are an uncommon and under‐reported presentation of cerebral hypoperfusion. Vascular etiology must remain on the differential as these transient but hemodynamically significant episodes are associated with severe carotid steno‐occlusive disease and carry an elevated risk for stroke. Methods The patient was evaluated in routine clinical practice. Results A man in his 50s with medical history of chronic right internal carotid artery (ICA) occlusion, coronary artery disease and tobacco use disorder presented with two months of intermittent, progressive worsening of left extremity tremors associated with ipsilateral weakness and mild confusion during the spells. These involuntary paroxysmal spells—precipitated by standing up, exertion and neck hyperextension—initially occurred 4 to 5 times per week in left upper extremity but progressed to 4 to 5 times per day with prolonged durations reaching 20 minutes and involving the left lower extremity. The initial event involved loss of consciousness, but no further syncopal episodes were noted. While ipsilateral hemiparesis and mild confusion occurred during the spells, spontaneous resolution and immediate return to baseline were reported afterward. On presentation, the National Institutes of Health Stroke Scale (NIHSS) was zero. Computed tomography (CT) head did not show acute intracranial process. CT angiography (CTA) re‐demonstrated right ICA occlusion at its origin. A load of Clopidogrel 300 mg and Aspirin 325 mg was administered. Orthostatic blood pressure measurements were normal. CT perfusion of brain demonstrated a perfusion decrease within the right frontoparietal lobes in the right middle cerebral artery (MCA) region. Routine EEG was performed, and it did not show interictal discharges. Brain MRI did not show acute infarcts. Catheter cerebral angiogram was then pursued, confirming right ICA occlusion at its origin and additionally showed mild atherosclerosis of the left ICA without flow‐limiting stenosis. After thorough evaluation, these events of unilateral extremity shaking and hemiparesis were deemed to be LS‐TIA. Neurosurgery was consulted and offered extracranial‐intracranial (EC‐IC)/ superficial temporal artery‐MCA bypass surgery. He was discharged in stable condition to continue DAPT and high‐dose statin while pending surgical intervention. Conclusion This case not only provides a descriptive narration of the presentation of LS‐TIA along with the steps in management undertaken but also encourages the consideration of vascular etiology as a potential cause for acute onset paroxysmal hyperkinetic movements. Early diagnosis and appropriate treatment are crucial to reduce burden of poor outcomes and prevention of stroke.